2013
DOI: 10.1002/phy2.9
|View full text |Cite
|
Sign up to set email alerts
|

Dietary saturated fat and docosahexaenoic acid differentially effect cardiac mitochondrial phospholipid fatty acyl composition and Ca2+uptake, without altering permeability transition or left ventricular function

Abstract: High saturated fat diets improve cardiac function and survival in rodent models of heart failure, which may be mediated by changes in mitochondrial function. Dietary supplementation with the n3-polyunsaturated fatty acid docosahexaenoic acid (DHA, 22:6n3) is also beneficial in heart failure and can affect mitochondrial function. Saturated fatty acids and DHA likely have opposing effects on mitochondrial phospholipid fatty acyl side chain composition and mitochondrial membrane function, though a direct comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
(120 reference statements)
0
8
1
Order By: Relevance
“…However, we noticed that cardiac linoleic acid (18:2), a primary precursor of AA, was lower after 6-month feeding among all SFA groups, suggesting a possible unconfirmed metabolic pathway responsible for the increased generation of AA. To a certain degree, changes in AA and linoleic acid in our study are inconsistent with the study performed by O’Connell et al [ 26 ], which suggested that, compared with low SFA diets, high SFA diets decrease cardiac subsarcolemmal mitochondrial linoleic acid, without causing significant alterations in AA. Differences in the fatty acid composition of diets, feeding duration and control group probably contribute to the inconsistencies between studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, we noticed that cardiac linoleic acid (18:2), a primary precursor of AA, was lower after 6-month feeding among all SFA groups, suggesting a possible unconfirmed metabolic pathway responsible for the increased generation of AA. To a certain degree, changes in AA and linoleic acid in our study are inconsistent with the study performed by O’Connell et al [ 26 ], which suggested that, compared with low SFA diets, high SFA diets decrease cardiac subsarcolemmal mitochondrial linoleic acid, without causing significant alterations in AA. Differences in the fatty acid composition of diets, feeding duration and control group probably contribute to the inconsistencies between studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have demonstrated that modulation of membrane fatty acid composition in the heart by dietary fats may affect membrane fluidity or permeability, phase behavior and membrane fusion, leading to the perturbations in membrane-bound enzymes and receptors, which ultimately impacts cardiac function [ 4 , 24 , 25 ]. In addition, dietary fat may also change cardiac mitochondrial phospholipid fatty acid side chain composition [ 26 ]. Neutral lipids, which mostly consist of triglycerides in mammalian cells, represent tissue lipid storage; while phospholipids, the most abundant lipid class in biomembranes, influence membrane properties and function [ 14 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, no differences were found in mitochondrial respiration capacity and kinetics, and it does not alter the OXPHOS protein content. This could be explained, in part, because despite the observed changes in membrane composition, no differences in membrane microviscosity and fluidity were observed [ 44 ]. In this study, the change in ω-3 fatty acids was at the expense of ω-6 fatty acids without modifying the content of saturated fatty acids, even in a high saturated fat diet, explaining the lack of observed effects in membrane fluidity.…”
Section: ω-3 Fatty Acids and Mitochondriamentioning
confidence: 99%
“…Their pathophysiology has been extensively studied and parallel many of the metabolic abnormalities that are seen in animals fed a high-fat diet [12]. Moreover, the fatty acid composition of certain high-fat diets might have independent mitochondrial effects, which could confound the mitochondrial phenotype [1315]. db/db mice were chosen to model extreme insulin resistance, obesity and diabetes.…”
Section: Introductionmentioning
confidence: 99%